Efektivitas Pelatihan Kognitif Perilaku Untuk Menurunkan Kecemasan Sosial Menjelang Masa Bebas Pada Narapidana Di Rutan Kelas I Surakarta - Yonitri, Dewi Arum, Dr. Nisa Rachmah N. A., M.Si., Psikolog, Rini Lestari, S.Psi, M.Si (2016)
Inmates nearing release certainly have hope can be received well by the public as before committing a crime. Initial survey results indicate overwhelmed by anxiety inmates nearing release. The causes of anxiety. Objective was to determine the effectiveness of cognitive behavioral training on social anxiety in class I Surakarta prison inmates. The study design menggunakkan quasi-experimental design in the form of non-randomized pretest-posttest control group design. The research subject inmates at the Detention Class I Surakarta numbered 20 people, divided into two groups: 10 people, including the experimental group and 10 people, including a control group. Collecting data using the anxiety scale social and cognitive behavioral training modules. Data were analyzed using K Related Samples Test Test Test Friedman and Mann Whitney U Test. The result of differences in score pre test, post-test and follow-up shows that there are differences in the level of social anxiety among the group given training (KE) with the group not given the training (KK). Social anxiety research subjects experimental group (KE) is lower than the control group (KK). Based on research, the Cognitive Behavioral Training interventions are effective in lowering the level of social anxiety to the inmates at the Detention Class I Surakarta.